PENINGKATAN NILAI CERNA SERAT DAN PENURUNAN THEOBROMIN POD KAKAO SEBAGAI BAHAN BAKU COMPLETE FEED PADA DOMBA - Wulandari, Suci ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The study consisted of three stages. In stage I, The Effects of Cacao Pod Fermentation with Microbial Inoculums on Fiber Composition, and Characteristics of Bacterial Isolates of Fermented Cacao Pod. Results showed that during pod cacao fermentation, there were an increased population of lactic acid and total bacteria, a lowered pH, an increased fiber digestibility, and reduced theobromine content. Changes in those parameters were found to be significant in cacao pods fermented and inoculated with the inoculums rate of 0.05%, 6 days fermentation time, and 40% water content. The highest reduction of theobromine in fermented cacao pods was 17.02%. The reduction of fiber and theobromine contents during the fermentation of cacao pods with bacteria inoculums was confirmed by the characteristics of bacterial isolates obtained from the fermented cacao pods. There were eight bacterial isolates found to be able to produce CMCase and Î²-glucosidase enzymes in various levels. Some isolates were also able to lower theobromine content in liquid culture by 27.07%. The best inoculums rate (0.05%) and fermentation time (6 days) with 40% water content obtained from stage I study were applied in the next stage. In stage II, Evaluation of Cacao Pod-based Complete Feed Inoculated with Microbial Inoculum and Its Effects on Rumen Microbial Fermentation. Anaerobic fermented complete feed with microbial Inoculum (CF2) was not able to make the fiber content of fermented complete feed lower than that of unfermented complete feed (CF0). After 24 hour rumen fermentation, each treatment gave different pH values of rumen liquid, namely 6.4 (CF1), 6.3 (CF2), and 6.3 (CF2). However, no differences were found in VFA concentration, ammonia concentration, and microbial protein content. It was shown that VFA and ammonia concentration was increased immediately after the feed was given to the animals. In stage III, Digestibility, Digestible Nutrients of Complete Feed, and Production Performance of Sheep. Results showed that there was no significant difference was found in OMD and digested organic matter (DOM). Mean fiber digestibility (FD) and digested fiber (DF) were significantly different. Compared to CF1 and CF2, unfermented complete feed (CF0) had the lowest DF. There were no different feed intake and daily weight gain (DWG) per unit of time were found. However, there was a tendency that sheep in CF2 gave the highest DWG and higher income over feed cost value (Rp 27,232 /head/month) than those fed unfermented cacao pods. It was concluded that microbial inoculum could be used as the source of microbes in fermentation process and reduction of fiber and theobromine in cacao pods (optimum rate was 0.05% and incubation time of 6 days with 40% water content).